2019
DOI: 10.1192/bji.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in Sierra Leone

Abstract: Sierra Leone is a West African country with a population of just over 7 million. Many Sierra Leoneans lived through the psychologically distressing events of the civil war (1991–2002), the 2014 Ebola outbreak and frequent floods. Traditionally, mental health services have been delivered at the oldest mental health hospital in sub-Saharan Africa, with no services available anywhere else in the country. Mental illness remains highly stigmatised. Recent advances include revision of the Mental Health Policy and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…The small number of individuals reported with MHD is of concern, especially given the high prevalence of anxiety, depression and post-traumatic stress disorder following the Ebola outbreak 8 . This finding may reflect underreporting and a persisting treatment gap for MHD 9, 10 .…”
Section: Discussionmentioning
confidence: 96%
“…The small number of individuals reported with MHD is of concern, especially given the high prevalence of anxiety, depression and post-traumatic stress disorder following the Ebola outbreak 8 . This finding may reflect underreporting and a persisting treatment gap for MHD 9, 10 .…”
Section: Discussionmentioning
confidence: 96%
“…Over 100 Community Health Officers have been trained in mhGAP, a package developed by the WHO to scale up prevention and management services for mental, neurological and substance use disorders in countries with low- and lower-middle incomes (WHO, 2016), but most are yet to receive any supervision or refresher training (Harris et al ., 2020). A roll-out of Psychological First Aid training for primary healthcare workers (Sijbrandij et al ., 2020) has lacked the follow-up that research has indicated is required to sustain a major uplift in capacity in this setting (Horn et al ., 2019).…”
Section: Understanding Mental Health In Sierra Leonementioning
confidence: 99%
“…However, authors do refer anecdotally to common terms for distress and mental illness in Sierra Leone, particularly crase and poil heart (e.g. Jones, 2008; Harris, 2007; Harris et al ., 2020). Crase is a Krio term indicating that someone is ‘crazy’, with poil heart (or pwɛl at ) indicating ‘heavy heartedness’ (Cavallera et al ., 2019: 121).…”
Section: Understanding Mental Health In Sierra Leonementioning
confidence: 99%
See 1 more Smart Citation
“…However, using prevalence rates from similar contexts, the treatment gap for this population is estimated to be 99.8–99.9% (6). Current specialized mental health services for children and adolescents are limited to one outpatient clinic at the Ola During Children’s Hospital in the capital Freetown, where services are provided by a mental health nurse who was trained in CAMH in Nigeria (7, 8). Three other nurses and four medical doctors were trained through the same program but are yet to be deployed in this capacity by the Government of Sierra Leone (S.K.…”
Section: Introductionmentioning
confidence: 99%